Β-blockers associated with reduced all-cause mortality in COPD. Issue 1 (26th September 2011) - Tashkin, Donald P
Abstract : Commentary on: Short PM Lipworth SI Elder DH . Effect of beta blockers in treatment of chronic obstructive pulmonary disease: a retrospective cohort study. BMJ 2011 ;342 :d2549 .